Use of the FITT framework to understand patients' experiences using a real-time medication monitoring pill bottle linked to a mobile-based HIV self-management app: A qualitative study. (November 2019) - Cho, Hwayoung; Flynn, Gabriella; Saylor, Maureen; Gradilla, Melissa; Schnall, Rebecca
Abstract: Objective: The purpose of this work was to conduct an in-depth analysis to understand patients' experiences using a real-time medication monitoring pill bottle linked to an HIV self-management app. Methods: A descriptive qualitative study design was used. In-depth interviews were conducted using a semi-structured interview guide at the 3-month follow-up visit during a trial of the app for improving medication adherence which began in January 2018. Eligibility criteria were HIV-positive, over the age of 18, ownership of a smartphone, able to speak and understand English and self-report less than 80% adherence to medications in the past 30 days or a viral load of over 20 copies/mL (detectable). All interviews were audio-recorded and transcribed. Using thematic analysis, we explored emerging themes with similar patterns across interviews and organized the themes according to the constructs of the Fit between Individuals, Task and Technology (FITT) framework. Results: Thirty-eight persons living with HIV (PLWH), who were randomized to the intervention arm of the study trial, participated in the interviews. 79.0% of participants reported their race as African American/Black, 63.2% had completed some high school or less, and 79.0% reported an annual median income of less than $20, 000. Data was collected until saturation was reached. A total of nine major themes organized by the FITT framework were identified. Three themes related to the fit between individuals and task were: motivation for strict medication adherence, self-efficacy for overall health management, and engagement with medication reminders. Four themes related to the fit between individual and technology were: ease of use, HIV-related stigma and disclosure of HIV status, customized alert of medication time windows based on individual routine set-up, and preference for device design. Two themes related to the fit between task and technology were: system functionality of data transfer from the electronic pill bottle to the app and self-awareness of system syncing signals. Conclusions: This study demonstrated that tracking medication adherence and receiving push-notification medication reminders through the electronic pill bottle connected to the app encourages and supports PLWH in adhering to their medication regimens. Findings from this work highlight the importance of adequate consideration of the needs of intended users in designing customizable mobile health technology, including HIV-related stigma, disclosure of HIV status and antiretroviral therapy regimens.